The Melanocortin-4 Receptor: Physiology, Pharmacology, and Pathophysiology - Tao, Ya-Xiong (The Endocrine Society, 2010)
The melanocortin-4 receptor (MC4R) was cloned in 1993 by degenerate PCR; however, its function was unknown. Subsequent studies suggest that the MC4R might be involved in regulating energy homeostasis. This hypothesis was confirmed in 1997 by a series of seminal studies in mice. In 1998, human genetic studies demonstrated that mutations in the MC4R gene can cause monogenic obesity. We now know that mutations in the MC4R are the most common monogenic form of obesity, with more than 150 distinct mutations reported thus far. This review will summarize the studies on the MC4R, from its cloning and tissue distribution to its physiological roles in regulating energy homeostasis, cachexia, cardiovascular function, glucose and lipid homeostasis, reproduction and sexual function, drug abuse, pain perception, brain inflammation, and anxiety. I will then review the studies on the pharmacology of the receptor, including ligand binding and receptor activation, signaling pathways, as well as its regulation. Finally, the pathophysiology of the MC4R in obesity pathogenesis will be reviewed. Functional studies of the mutant MC4Rs and the therapeutic implications, including small molecules in correcting binding and signaling defect, and their potential as pharmacological chaperones in rescuing intracellularly retained mutants, will be highlighted.